ANALISIS PENGGUNAAN APLIKASI E-VOTING PEMIRA UNIVERSITAS HALU OLEO: PERLUASAN TECNOLOGY ACCEPTANCE MODEL DENGAN TRUST IN INTERNET SEBAGAI VARIABEL MODERATOR - Fazlul Rachmat Mubbaraq; Natalis Ransi; Ferdinand Murni Hamundu (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2024)
This study aims to conduct an in-depth analysis of the level of acceptance of the e-voting application in the Halu Oleo University PEMIRA using TAM. This research is a quantitative research, using the SPSS application.The Technology Acceptance Model (TAM) is a framework that can be used to understand user behavior towards technology. TAM is a model that explains how technology users accept and use it. According to this theory, a person's behavior model is influenced by behavioral goals. The attitude towards the behavior determines the purpose of the behavior. In this context, the variables used are perceived usefulness and perceived ease of use, Attitude Toward Using, Behavioural Intension to Use Actual Use and Trust In Internet.  Of the 6 variables, there are 8 hypotheses and of  these 8 hypotheses 7 hypotheses are accepted and the rest are rejected. Based on the results of the analysis, trust in the internet is able to moderate the relationship between perceived usefulness and behavior to use, the contribution of the influence of the PU variable on the BITU variable after the moderation variable is 97.3%.